LAND USE AND LAND COVER IN THE MACABU RIVER WHATERSHED (RJ): IMPACTS ON THE LANDSCAPE AND WATER AVAILABILITY (VERUM: Journal of Scientific Initiation, 2026)
This research analyzes the impacts of landscape transformations on water availability, based on the assessment of land use and land cover in the Macabu River Watershed (BHRM), located in the state of Rio de Janeiro. It is based on the assumption that the increase in anthropogenic influence, combined with the absence of integrated territorial planning, has altered the local hydrological dynamics, compromising water regulation and intensifying socio-environmental impacts. The study adopted the historical-geographical method, seeking to understand territorial transformations over time. The identified consequences include channel siltation, loss of wetlands, increased environmental fragility, and heightened vulnerability of local populations. The results indicate that water-related issues in the BHRM are intrinsically linked to the way the territory has been historically occupied and managed, which reinforces the need for actions aimed at the geoenvironmental restoration of the watershed, fostering a culture of water sustainability and socio-environmental justice.
Keywords: Land Use and Land Cover; Water Availability; Landscape Transformations